Effect of Bluebox E-commerce Service Quality on User Satisfaction Using Webqual 4.0 and End User Computing Saticfaction (EUCS) methods - Irna Awalia Febriyanti; Lion Ferdinand Marini; Lorna Yertas Baisa (Eduvest - Journal of Universal Studies, 2024)
Bluebox is the first online shopping platform in Manokwari that provides a wide range of daily and monthly shopping products not only that but also food and snacks, which can help the shopping process from home. Bluebox comes with delivery services in various areas in Manokwari and offers various payment options, including COD, transfer, and QRIS. The purpose of this study is to investigate in depth how the Bluebox application can improve their service quality from various aspects based on user satisfaction and experience with the ultimate goal of increasing user satisfaction and the success of MSMEs in Manokwari. The data is processed using the Webqual 4.0 method which includes Usability, Information Quality, service Interaction variables and the End User Computing Satisfaction (EUCS) method, especially the Timeliness variable. The data analysis method in this study uses the PLS-SEM approach with SmartPLS version 4.1.0.2 as a tool to help test research data. From the test results obtained in this study, each of the four hypotheses proposed that the average measurement of user satisfaction with the Bluebox application gets a value of 4.095 with the Satisfied category. Factors that affect user satisfaction with 4 hypotheses and 1 acceptable hypothesis, namely the Timeliness variable which has a significant effect of P Values <0.05 on User Stisfaction, while the Usability, Information Quality and Service Interaction variables do not show a significant effect on User Satisfaction with a significance level of P Values> 0.05 in the Bluebox application.